Model of Intellectual Capital and Locus of Control on the Performance of Public Sector Internal Auditors Through Professional Commitment - Nurdiana Mulyatini; Suryana Sumantri; Umi Narimawati (Journal of Management Review, 2019)
The development of a paradigm towards good governance requires government officials who are responsive to bureaucratic reform demands by changing ways of working and behavior characterized by a high level of performance, accountability, transparency, clean from corruption, collusion and nepotism. The purpose of this research is to develop the model of Intellectual Capital and Locus of Control to improve the performance of Public Sector Internal Auditors through professional commitment. The benefits of this research are expected to contribute and respond to various problems in the implementation of organizational governance in the field of supervision through strengthening performance-based internal auditors' behavior so that they are able to work objectively and independently in investigations for preventive prevention of practices fraud. The results of the study provide an overview of intellectual capital (human capital, organizational capital and consumer capital) and locus of control both internally and externally affect the strengthening of professional commitment (affective, continuous, normative) and have implications for the high performance of internal public sector auditors. The relationship is illustrated in the path diagram model of 30 Government Internal Supervisors in the district / city inspectorate in West Java Province.